Correlation of tumor necrosis factor-α and interleukin-1 single-nucleotide polymorphisms with the risk of migraine development - Guijiao Huang; Xin Dong; Xiaojiao Shao; Mengping Wu; Shan Gao; Yixuan Wang; Xinying Guan (Frontiers in Genetics)
BackgroundMigraine, a condition stemming from neurological and vascular irregularities with inflammation involvement, was investigated in a case-control study focusing on the Chinese Han population.MethodsThe research analyzed specific genetic variations—TNF-α −308 G/A, TNF-α −857 C/T, TNF-α −238G/A, IL1B-3953 C/T, and IL1RN −2018T/C SNPs—within 212 migraine patients and 210 healthy controls. Utilizing SNaPshot technology, scientists genotyped these markers related to TNF-α and IL-1 genes.ResultsFindings revealed a significant association between the IL1B−3953 C/T SNP and migraine susceptibility, particularly noting its link with a familial history of the disorder. The presence of the C allele at this location was more prevalent in migraine sufferers. Multivariate analysis reinforced this connection, indicating the C allele under a dominant model as an independent risk factor for migraine (OR = 2.315, 95%CI: 1.053–5.090, P = 0.037). Additionally, the study observed a sex-specific difference regarding the TNF-α −857 C/T SNP among migraine patients.ConclusionOverall, this investigation contributes to understanding the genetic underpinnings of migraine in the Han Chinese population, highlighting the IL1B−3953 C/T SNP as a potential biomarker for migraine susceptibility.